Geo-spatial hotspots of hemorrhagic fever with renal syndrome and genetic characterization of Seoul variants in Beijing, China. - Shu-Qing Zuo; Li-Qun Fang; Lin Zhan; Pan-He Zhang; Jia-Fu Jiang; Li-Ping Wang; Jia-Qi Ma; Bing-Cai Wang; Ri-Min Wang; Xiao-Ming Wu; Hong Yang; Zhi-Wei Cao; et al. (Public Library of Science (PLoS), 2011)
BACKGROUND: Hemorrhagic fever with renal syndrome (HFRS) is highly endemic in mainland China, and has extended from rural areas to cities recently. Beijing metropolis is a novel affected region, where the HFRS incidence seems to be diverse from place to place. METHODOLOGY/PRINCIPAL FINDINGS: The spatial scan analysis based on geographical information system (GIS) identified three geo-spatial "hotspots" of HFRS in Beijing when the passive surveillance data from 2004 to 2006 were used. The Relative Risk (RR) of the three "hotspots" was 5.45, 3.57 and 3.30, respectively. The Phylogenetic analysis based on entire coding region sequence of S segment and partial L segment sequence of Seoul virus (SEOV) revealed that the SEOV strains circulating in Beijing could be classified into at least three lineages regardless of their host origins. Two potential recombination events that happened in lineage #1 were detected and supported by comparative phylogenetic analysis. The SEOV strains in different lineages and strains with distinct special amino acid substitutions for N protein were partially associated with different spatial clustered areas of HFRS. CONCLUSION/SIGNIFICANCE: Hotspots of HFRS were found in Beijing, a novel endemic region, where intervention should be enhanced. Our data suggested that the genetic variation and recombination of SEOV strains was related to the high risk areas of HFRS, which merited further investigation.